Acoustic Comfort Evaluation in Traditional Houses and its Impact on Inhabitant Satisfaction in the City of Sulaimani - Shilan Ameen Mustafa; Banaz Nasraldeen Muhealdeen (UHD Journal of Science and Technology, 2023)
Acoustic comfort is one of the essential needs for people to live in calm and comfort in dwellings. Because of technological and industrial development, noise pollution became one of the big dangers that impacts human psychologically and physiologically. The historical neighborhoods in Sulaimani City are affected by this technological advancement, the demolishing of traditional houses and changed to commercial has increased the environmental noise. Therefore, this research aims to evaluate residents’ satisfaction in traditional houses in term of acoustic conditions, also aims to investigate if the design characteristics of traditional houses have role in providing acoustic comfort, and to promote traditional designs in today’s architecture. The absence of a practical study evaluating acoustic conditions in traditional houses and their impact on inhabitants’ satisfaction in Sulaimani city formed the main problem of the research. The results from the questionnaire and the in situ measurements have shown that, although most of these old houses were demolished and changed to commercial areas, the acoustic environment inside most houses is comfortable and most inhabitants are satisfied with the acoustic conditions. The traditional design turned the houses to be a barrier against transmitting noise whether from outside to inside or vice versa.